Incidental Flexor Carpi Radialis Tendinopathy on Magnetic Resonance Imaging. (September 2019) - Stoop, Nicky; van der Gronde, Bonheur A. T. D.; Janssen, Stein J.; Kuntz, Michael T.; Ring, David; Chen, Neal C.
Background: Wrist pain is often nonspecific. Magnetic resonance imaging (MRI) is regularly obtained to evaluate wrist pain. Variations and pathophysiology identified on MRI may not account for patient's clinical symptoms. This study aims to quantify the prevalence of flexor carpi radialis (FCR) tendinopathy on MRI and the coexistence of trapeziometacarpal (TMC) or scaphotrapeziotrapezoid (STT) osteoarthritis.Methods: Using an institutional research database, we identified 3631 adult patients who obtained an MRI of the wrist during a 15-year period. Text search in the radiology reports identified 302 patients with possible FCR signal abnormalities. After reviewing the medical records, 98 patients were identified with FCR tendinopathy. Furthermore, medical records were used to identify pain located on the volar radial part of the wrist. In the absence of a documented examination consistent with FCR tendinopathy, we considered any signal change in the FCR incidental.Results: We identified 55 patients (55%) with incidental FCR tendinopathy. In a bivariate analysis, we found FCR signal changes on the MRI were associated with older age, white race, clinically suspected FCR tendinopathy, volar-radial sided wrist pain, and TMC and STT arthritis. Using multivariable logistic regression to account for confounding, older age and volar-radial sided wrist pain were independently associated with FCR signal changes on MRI.Conclusions: Signal changes in the FCR are infrequent and often incidental (asymptomatic) or associated with peritrapezial osteoarthritis.